Research on the Integration and Innovative Development Path of Cross border Cultural Communication of English Tour Guides Driven by the Dual Wheel of "AI+Big Data" - Li, Wenjing (Journal of Artificial Intelligence and Information, 2025)
With the rapid development of technology, "AI+big data" has become an important force driving changes in various industries and plays a key role in the tourism industry. For English tour guides, who bear the responsibility of cross-border cultural dissemination, "AI+big data" brings new opportunities and challenges. This article deeply analyzes the current application status of "AI+big data" in cross-border cultural communication of English tour guides, explores the advantages brought by its integration and innovation, such as precise communication and diversified content, and analyzes the problems faced by insufficient technological application capabilities. On this basis, an integrated and innovative development path has been proposed, including enhancing the digital literacy of tour guides, optimizing cultural communication content creation, and strengthening cross-cultural communication and interaction, aiming to help English tour guides better utilize "AI+big data" to carry out cross-border cultural communication in the new era and enhance the international influence of Chinese culture.